TINJAUAN TENTANG PEMAHAMAN KESELAMATAN DAN KESEHATAN KERJA SISWAPADA PRAKTEK KERJA KAYU KELAS XI DAN XII PROGRAM KEAHLIAN TEKNIK BANGUNAN KOMPETENSI KEAHLIAN TEKNIK KONSTRUKSI KAYU SMK NEGERI 2 SAWAHLUNTO - 1136-1153 , Zamrud Kurnia (Universitas Negeri Padang, 2016)
ABSTRAKEngineering Program with Competencies Skills Building Construction Engineering Wood SMKN 2 Sawahlunto special moves on the field of timber. The fundamental problem in woodworking is an accident that occurred while working in the workshop. Based on information from the chairman of the Department of Buildings, occupational accidents have occurred in 2005 and 2006. In addition, from the interviews is known that wood workshop SMKN 2 Sawahlunto not yet meet the standards of a good workshop. For that I am interested in doing research with the title: Overview of understanding of occupational safety and health technical students in wood XI and XII graders Engineering Program Skills Competency Building Construction Engineering Wood SMKN 2 Sawahlunto.This type of research is descriptive. The population in this study were students of class XI and XII Engineering Program Skills Competency Building Construction Engineering Wood N 2 Sawahlunto, amounting to 22 students. The sampling technique in this study using total sampling method. Data collection tool is questionnaire and data were processed using the statistical program SPSS version 17.0.The results showed that: understanding of occupational safety and health in the implementation of the wood work practices class XI and XII Engineering Program Skills Competency Building Construction Engineering Wood SMKN 2 Sawahlunto with the average value of K3 at 70.64% against themselves, on average K3 to the tools and equipment 74.27% and an average of 79.71% K3 to the environment. based on research results throughout degrees of achievement in the category